Nonisothermal crystallization kinetics of poly(lactide)—effect of plasticizers and nucleating agent. Issue 5 (31st October 2012) - Courgneau, Cécile; Ducruet, Violette; Avérous, Luc; Grenet, Jean; Domenek, Sandra
Abstract Poly(lactide), a bio‐based aliphatic polyester, is a subject to large research effort. One point of optimization is the acceleration of its crystallization kinetics to promote crystallinity under nonisothermal polymer processing conditions by means of compounding with nucleating agents and plasticizers. The nonisothermal crystallization kinetics of neat and formulated poly(L, D‐lactide) (PDLLA) from the melt with talc and polyethylene glycol (PEG) or acetyl tributyl citrate (ATBC) were studied with the help of the Avrami–Jeziorny and Liu–Mo analysis. Talc showed to be a moderately efficient nucleating agent, as it causes only small increase of crystallization kinetics and shows no effect on the crystallization activation energy. A synergistic effect with plasticizers was observed, expanding the crystallization window significantly. PEG was found to be a more efficient plasticizer than ATBC but causes large decrease in the molecular weight average of PDLLA upon thermal treatment. The talc/ATBC system is efficient starting with an ATBC concentration of 9 wt%. The acceleration observed was a crystallization half‐time decrease of 30% compared to neat PLA and reaching maximum crystallization enthalpies even at cooling rate of 25°C min−1. The ATBC/talc system can be recommended as an efficient system for acceleration of nonisothermal crystallization kinetics of PDLLA. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers